Complete plastome sequence of Arisaema ringens (Araceae): a dioecious herb disjunctly distributed in China, Japan and Korea. Issue 1 (2nd January 2019) - Cai, Xiu-Lian; Wang, Jian-Hua; Zhao, Kun-Kun; Wang, Hong-Xin; Zhu, Zhi-Xin; Wang, Hua-Feng
Abstract: Arisaema ringens is a dioecious herb of the family Araceae. So far, there have been no studies on the genome of A. ringens. Here we report and characterize the complete plastid genome sequence of A. ringens in an effort to provide genomic resources useful for promoting its conservation. The complete plastome is 160, 792 bp in length and contains the typical structure and gene content of angiosperm plastome, including two inverted repeat regions of 25, 312 bp, a large single copy region of 88, 915 bp, and a small single copy region of 21, 253 bp. The plastome contains 114 genes, consisting of 80 unique protein-coding genes, 30 unique tRNA genes, and 4 unique rRNA genes. The overall A/T content in the plastome of A. ringens is 63.50%. The complete plastome sequence of A. ringens will provide a useful resource for the conservation genetics of this species as well as for the phylogenetic studies for Araceae.